The effect of high performance work system strength on organizational effectiveness: Opportunities for international joint ventures by foreign firms. Issue 1 (16th December 2019) - Dayarathna, Dushar Kamini; Dowling, Peter John; Bartram, Timothy
Abstract : Purpose: This paper aims to examine the implications of high performance work system (HPWS) strength from a managerial perspective and the impact of economic, cultural, political, legal and technological factors on the operationalization of HPWSs in the banking industry in Sri Lanka. Design/methodology/approach: The data for this study were collected from three licensed commercial banks in Sri Lanka. This research used a case study approach for data collection with archival analysis of records and semi-structured interviews with the CEO, head of HR, two board members and three focus groups (top, middle and lower level managers across various functional areas) in each bank which altogether covers 66 key informants. Findings: The findings supported the research proposition that to gain positive outcomes on organizational effectiveness, there should be a strong HPWS, resulting in a positive attitudinal climate among employees. Further, the findings provide evidence of the global applicability of HPWSs, although more research is needed to clearly specify the contextual boundaries of HPWS effectiveness. Originality/value: Contemporary research provides ample evidence to endorse the contribution of high performance work systems toward organizational effectiveness. However, there is a dearth of literature on how high performance work systems are operationalized across the management hierarchy and support the achievement of organizational effectiveness. Few studies have been conducted on high performance work system strength and organizational effectiveness in emerging economies.